A Comparative Study on Retirement Process in Korea, Germany, and the United States: Identifying Determinants of Retirement Process. (October 2016) - Cho, Joonmo; Lee, Ayoung; Woo, Kwangho
This study classifies the retirement process and empirically identifies the individual and institutional characteristics determining the retirement process of the aged in South Korea, Germany, and the United States. Using data from the Cross-National Equivalent File, we use a multinomial logistic regression with individual factors, public pension, and an interaction term between an occupation and an education level. We found that in Germany, the elderly with a higher education level were more likely to continue work after retirement with a relatively well-developed social support system, while in Korea, the elderly, with a lower education level in almost all occupation sectors, tended to work off and on after retirement. In the United States, the public pension and the interaction terms have no statistically significant impact on work after retirement. In both Germany and Korea, receiving a higher pension decreased the probability of working after retirement, but the influence of a pension in Korea was much greater than that of Germany. In South Korea, the elderly workers, with lower education levels, tended to work off and on repeatedly because there is no proper security in both the labor market and pension system.